Challenging Everyday Monogamism: Making the Paradigm Shift From Couple-Centric Bias to Polycule-Centred Practice in Counselling and Psychotherapy - Y. Gavriel Ansara (Psychotherapy and Counselling Journal of Australia)
Monogamism is the systemic oppression enacted through ideas and practices that valorise monogamous people and relationships while systematically devaluing polyamorous and multi-partnered ones. One manifestation of monogamism is mononormative bias: the bias that all people are or should be monogamous and that multi-partnered relationships are "alternative," "different," immature, or rare. Couple-centric bias is a type of mononormative bias that assumes all people desire or should have a "couple" relationship, and that other relationship configurations are inferior, immature, unnatural, abnormal, or unsustainable. Everyday monogamism refers to the unexamined implicit and explicit monogamist biases and systemic oppression that people in polyamorous relationship systems and multi-partnered kinship bonds navigate in everyday life. This paper explores everyday monogamism in counselling and psychotherapy. In this article, I critique some everyday language, concepts, and clinical practices through which therapists—particularly relationship counsellors—enact monogamist oppression. Next, I challenge the couple-centric bias endemic to both explicitly monogamist and ostensibly polyamory-inclusive relationship counselling approaches. Finally, I discuss how therapists can participate in the ongoing paradigm shift from couple-centric bias toward polycule-centred practice.